Aumento da atividade celulásica para hidrólise da casca de coco verde pela aplicação da alta pressão hidrostática - Albuquerque, Érica Dutra (2013)
The use of cellulosic biomass for cellulosic ethanol production has been a serious option for the production of renewable fuels. The main focus in the cellulosic ethanol production is to increase the hydrolysis of these cellulosic materials in order to produce products with a low-molecular weight, such as hexoses.The high costs involved with this process due to the use of cellulases and the biomass pretreatment, causes the main problem in an economically viable large-scale production of bioethanol. Even though enzymatic disruption of cellulose has been considered the best environmental practice, cellulase is the most expensive step during cellulosic ethanol production. Another problem is the inhibition of the cellulase complex by reducing-sugars such as cellobiose and glucose. Significant cost-reduction becomes needed in order to enhance viable commercial use of cellulase hydrolysis technology. Using coconut husk as a biomass substrate, we applied two approaches: firstly, we isolated fungi from coconut husks. We found that their cellulases outperforme the cellulases of the industry standards on the hydrolysis of coconut husk. Secondly, we employed High Hydrostatic Pressure (HHP) to the cellulases in order to improve the enzymatic performance. After the HHP treatment, we observed an increase in coconut husk hydrolysis by a factor of 2 as a result of an increase of the βglucosidase, endoglucanase and total cellulase activities. The effect of HHP is able to break the hydrogen bonds working down to the scales of the coconut fibers. Further, the inhibition of β-glucosidases caused by glucose was removed under HHP, the βglucosidases achivied higher activities in the presence of 55 mM of glucose as a result of changes in the conformation of this cellulase on HHP. Using bioinformatics tools to analyse structures of β-glucosidase and endoglucanase, we found hydrophobic aminoacids and glycosylation regions in the cavities; in the active sites; and on β-sheets structures. While HHP affects the cavities of the proteins, the carbohydrates can bind both to their side chains of hydrophobic amino acids as to glycosylation regions, leading to an increase of the activities and a stabilization of the protein. HHP to value of 300 MPa exposes the internal apolar parts of the coconut fiber (CEF) and favors the binding of hydrophobic aminoacids of the cellulase to these parts of the fibers, as well as to glucose. The increase of the cellulase hydrolysis under HHP can be caused by a factor that works like a CBM (Carbohydrate Binding Module) that approaches the substrate at the active site. Thus, employing both the 21 technologies HHP as well as substrate specific fungi can potentially make bioethanol production an economic viable and energy-efficient process, especially regarding the improvement of β-glucosidase activities.